2014
DOI: 10.1016/j.jaac.2013.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Patterns of Anxiety From Childhood to Adulthood: The Great Smoky Mountains Study

Abstract: Objective-The aims of this study were twofold: 1) to provide a brief introduction to the prospective, longitudinal Great Smoky Mountains Study and review recent findings; and 2) to use this sample to conduct an epidemiologic analysis of common childhood anxiety disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
354
2
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 500 publications
(383 citation statements)
references
References 48 publications
16
354
2
11
Order By: Relevance
“…age 13) to develop intrusive worries. The sex differences found in our analyses endorse previous research (Copeland et al, 2014, Muris et al 1998Silverman et al, 1995), with the only difference being the age at which the differences were found: Muris and colleagues (2002) found more anxious thoughts in girls compared to boys in 7-9 year olds, while our sample reported differences from age 10 onwards. However, our sexspecific findings map well onto patterns identified for rumination, which is defined as a repetitive and passive thinking pattern and shows considerable conceptual overlap with worrying (Jose & Brown, 2008).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…age 13) to develop intrusive worries. The sex differences found in our analyses endorse previous research (Copeland et al, 2014, Muris et al 1998Silverman et al, 1995), with the only difference being the age at which the differences were found: Muris and colleagues (2002) found more anxious thoughts in girls compared to boys in 7-9 year olds, while our sample reported differences from age 10 onwards. However, our sexspecific findings map well onto patterns identified for rumination, which is defined as a repetitive and passive thinking pattern and shows considerable conceptual overlap with worrying (Jose & Brown, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…It is important to note that at age 10, British children typically are preparing to transfer from primary to secondary school, which could partially explain the high frequency of worries at 10, especially the high prevalence of worry about schoolwork. The heightened mother-perceived interference despite the reduced frequency of worries at 13 could be explained by the increased cognitive maturation at this age, which might be a requisite for elevated interference (Muris, 2006) and further explain heightened vulnerability for intrusive levels of worrying in early adolescence (Beesdo et al, 2009, Copeland et al, 2014, Kertz & Woodruff-Borden, 2011. Although further inquiry is needed, the level of interference in daily activities and emotional disruption due to normal worries, independent of the level of worry frequency, might be key in early identification of intrusive worries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety disorders are among the most prevalent psychiatric disorders in children and adolescents and predict great burden into adulthood (Copeland et al, 2014;Merikangas et al, 2010;Weems and Silverman, 2013;Woodward and Fergusson, 2001). Separation, social, and generalized anxiety disorder (GAD) are particularly common among youth, with relatively early ages of onset and high rates of co-occurence with each other (Mohatt et al, 2014;Verduin and Kendall, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Some factors that predicted persistence were potentially tractable, such as neurodevelopmental disorder, intellectual disability and parental psychopathology. In the Great Smoky Mountain Study, a population-based overlapping cohort study of children aged 9-13 years; those with childhood psychiatric disorder were three times as likely to have a disorder in subsequent waves in childhood as well as adulthood (Costello et al 2003;Copeland et al 2014). Similarly, half of the adults with psychiatric disorder at age 26 years in the prospectively studied Dunedin cohort had a psychiatric disorder before the age of 15 years, increasing to three quarters by age 18 years, and higher still among mental health service users in adulthood (Kim-Cohen et al 2003).…”
Section: Editorial Emotional and Behavioural Difficulties And Mental mentioning
confidence: 99%